Analysis of defects dominating carrier recombination in CeO2 single crystal for photocatalytic applications - Zhang, Endong; Brabec, Christoph; Kato, Masashi (Journal of Physics D: Applied Physics, 2024)
In photocatalytic water splitting and CO2 reduction, recently, cerium oxide (CeO2) has been widely investigated. Defects that can directly dominate carrier recombination are essential for the photocatalytic performance of CeO2. In this study, several photoluminescence (PL) peaks are observed on the (100) face of an undoped CeO2 single crystal, indicating the presence of defects. Moreover, we characterize carrier recombination using time-resolved photoluminescence (TR-PL) and microwave photoconductivity decay (μ-PCD) measurements. The temperature dependence of decay curves is the result of carrier trapping and emission at deep levels. These decay curves are observed separately using a 565 nm band-pass filter (BPF) based on the PL spectra. The trap energy level ( E T ) and majority carrier capture cross-section ( σ T ) of each defect are also analyzed using rate equations to fit the experimental results. The temperature-dependent time constants are well reproduced by a recombination model using hole traps HTinfrared and HTvisible at E T of 0.76 and 0.55 eV from the conduction or valence band, with estimated σ T of the order of 10−21 and 10−22 cm2 for without and with the BPF, respectively. These findings regarding the presence of multiple defects in a single crystal indicate the necessity to focus on defect control.
CRIS-Team Scopus Importer:2025-02-04
Keywords: carrier recombination; CeO; defect analysis; photocatalyst; single crystal